Um modelo de produção de pares na dinâmica de Boltzmann. - Venturim, Alexandre Dalcomune (2020)
The Boltzmann equation is an equation widely used to extract information about the transport phenomena of physical systems, such as the electrical conductivity of plasma, which has great importance for different types of applications. In this work, some i